Gagueira: relação entre grau de severidade com características vocais e configuração do trato vocal - Caputo, Mirela Silveiro Pollini (2017)
Introduction: Studies on the vocal and laryngeal aspects of people who stutterer began to be investigated in the 70's. However, in the researched literature were not found publications with a complete voice assessment, considering the auditory and acoustic perceptual aspects along with the analysis of the vocal tract configuration with varying degrees of severity of stuttering. Objective: to describe perceptual, acoustic and vocal tract aspects in a group of subjects with different degrees of stuttering severity. Method: The sample consisted of five male adults, between 20 and 36 years old, with stuttering, each with one degree of severity (very mild, mild, moderate, severe and very severe). In order to determine the degree of severity, they took the Stuttering Severity Instrument 4, and answered a self-evaluation based on the same instrument. The voice of each subject was recorded in an acoustically treated voice laboratory and the nasofibrolaryngoscopic exams were performed by the otorhinolaryngology team of the same institution. For the auditory perceptual evaluation, were used the isolated vowels, the semi-directed speech sample and the reading of a phonetically balanced text with specific protocol. The general grade, roughness, soprosity, tension, and the instability were investigated by means of an analogue scale. In the acoustic analysis, isolated vowels and carrier sentences were used to extract the fundamental frequency (f0), jitter, shimmer, the first three formants and the voice onset time (VOT). The vocal tract configuration was tested with adapted protocol for singing voice and the configuration of the following structures and musculature were analyzed: vocal folds, supraglote, pharynx, tongue and larynx in vertical mobility. Results: in the auditory perceptual evaluation of the voice the two subjects with severity degrees severe and very severe presented a discrete to moderate degree of alteration in all the items investigated except for roughness, which was not presented by any subject. In the acoustic analysis for f0, in both vowels the value was below the reference in four of the five subjects, the same happening for jitter and shimmer. The first and second formants had lower values than did fluent speakers as reported in the literature. And in F3 the findings were varied. VOT was below the reference in all subjects with the exception of the one that was severe, who had the VOT value below only in the third formant. In the vocal tract analysis, it was observed that the higher the degree of severity the greater the number of alterations in stuttered speech, mainly in the supraglottis, pharynx and vertical laryngeal mobility. Conclusion: in the five cases analyzed, it was evident that there is a relationship between the degree of severity and the vocal aspects and configuration of the vocal tract. The three subjects with moderate, severe and very severe degrees of severity presented more changes in the three evaluated aspects